2022
DOI: 10.3389/fdgth.2022.899643
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Electronic Adherence Monitors and Associated Interventions for Routine HIV Antiretroviral Therapy in Uganda: Promising Findings

Abstract: BackgroundHigh, sustained adherence is critical for achieving the individual and public health benefits of HIV antiretroviral therapy (ART). Electronic monitors provide detailed adherence information and can enable real-time interventions; however, their use to date has largely been confined to research. This pilot study (NCT03825952) sought to understand feasibility and acceptability a relatively low-cost version of this technology and associated interventions for routine ART delivery in sub-Saharan Africa.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Similar to what we found in our study, these studies also identified technology and tools as a prominent barrier to implementation. Patients identified issues with device connectivity 19,31 and with alarms being either inappropriate or obtrusive. 27,35,37 Other qualitative studies also highlight patient-reported issues with device portability during commuting or travel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to what we found in our study, these studies also identified technology and tools as a prominent barrier to implementation. Patients identified issues with device connectivity 19,31 and with alarms being either inappropriate or obtrusive. 27,35,37 Other qualitative studies also highlight patient-reported issues with device portability during commuting or travel.…”
Section: Discussionmentioning
confidence: 99%
“…Our study's focus on implementation of technologically enabled pillboxes at the time of hospital discharge adds to existing qualitative studies in the ambulatory setting. 19,22,[27][28][29][30][31][32][33][34][35][36] These studies have examined the use of a smart pillbox in a variety of geographic locations (e.g., U.S. academic medical centers, clinics in sub-Saharan Africa, urban clinics in India) for a variety of conditions. Similar to what we found in our study, these studies also identified technology and tools as a prominent barrier to implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies examined the application of the CFIR in both pre- and post-implementation stages. These studies have demonstrated the strengths of utilizing the CFIR in various types of research, including qualitative [ 54 , 55 , 65 67 , 69 , 71 , 73 , 75 , 77 , 79 ], quantitative [ 53 ], mixed methods [ 76 ] and case studies [ 72 ]. Qualitative studies have employed the CFIR as an interview design and guide and collection tool to explore the perspectives and engagement of healthcare system stakeholders concerning implementation readiness [ 54 , 55 , 65 67 , 69 , 71 , 73 , 75 , 77 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In LMIC settings, digital solutions have provided a means to ensure that data could be reliably collected from decentralized testing sites ( 12 , 13 ). While digital solutions have often served a similar function in other disease responses in Uganda in the past ( 12 , 13 ), the national e-Health and data management strategy highlights that these tools have often been fragmented, with limited scale-up outside of individual projects ( 14 ).…”
Section: Introductionmentioning
confidence: 99%